Theatre and role play - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Theatre is a good way to help awareness-building, since it can encourage a process of reflection, reaction and action (see Spore 78). In Soulou, Burkina Faso, theatre is used as a technique to resolve issues of land allocation to landless...